Conceptions and Practices of Autonomy among Indigenous and Peasant Movements in Latin America - Barbosa, Lia Pinheiro; Rosset, Peter Michael [UNESP] (Sage Publications Inc, 2024)
This paper seeks to categorize the forms of autonomy developed by Indigenous and peasant movements in Latin America into three types: a) de jure autonomies versus de facto autonomies; b) explicit autonomies versus implicit autonomies; and c) (mono)ethnic autonomies versus popular or class autonomies. We argue that the debate between these conceptions takes on a possible strategic importance when it comes to the dialogue between Indigenous and peasant struggles regarding the defense of territory as well as in the conception of peasant autonomy, understood as a strategy of struggle and local self-governance.
Keywords: Autonomy; Social movements; Peasantry; Indigenous peoples; Latin America